Pregabalin to improve postoperative recovery in bariatric surgery: A parallel, randomized, double-blinded, placebo-controlled study - Martins, Marcelo J. [UNESP]; Martins, Caroline Paiva Matos Oliveira; Castro-Alves, Lucas J.; Jesus, Gabriel Nascimento; Campos, Guilherme Oliveira; Sacramento, Breno Barbosa Cerqueira; Borges, Leonardo Ferrari; Mello, Carlos Augusto Bastos; Alves, Rodrigo Leal; Módolo, Norma Sueli Pinheiro [UNESP] (Taylor & Francis, 2018)
Purpose: Obesity has been considered as a major public health problem in developed countries for which bariatric surgery has become an important treatment strategy. Postoperative pain, however, is a frequent problem in postoperative management. Pregabalin blocks the development of hyperalgesia and central pain sensitization. The objective of this randomized, placebo-controlled, double-blinded trial was to evaluate the effect of a single dose of preoperative pregabalin vs placebo on the quality of postoperative recovery in patients undergoing bariatric surgery. Patients and methods: A total of 70 patients undergoing abdominal gastroplasty were randomly assigned to receive oral pregabalin (75 mg) or an identical placebo 1 hour before surgery. The primary outcome was Quality of Recovery-40 (QoR-40) score at 24 hours. Secondary outcomes included opioid consumption and postoperative pain scores. P<0.05 was considered to indicate statistical significance. Results: In all, 60 of the 70 patients completed the study. The mean (SD) global recovery scores (QoR-40) 24 hours after surgery in the pregabalin and control groups were 183.7 (9) and 182.1 (12), respectively (mean difference=1.6, 95% CI –7.36 to 4.2, P=0.59). There was no significant difference in the total opioid consumption in the 24 hours following surgery between the two groups (pregabalin vs control=0.47×0.2; mean difference=0.26, 95% CI −0.24 to 0.77, P=0.3). There were no significant differences in nausea, vomiting, or time to postanesthesia care unit discharge between the two groups. Conclusion: In patients who underwent bariatric surgery, a single preoperative dose of pregabalin (75 mg) did not improve pain relief, quality of postoperative recovery, or reduction in opioid consumption. Clinical trial registration: http://www.ensaiosclinicos.gov.br (identifier: RBR-2g89x8).
Keywords: Gastroplasty; Hyperalgesia; Opioid